2012
DOI: 10.1016/j.cell.2012.03.046
|View full text |Cite
|
Sign up to set email alerts
|

LINC Complexes Form by Binding of Three KASH Peptides to Domain Interfaces of Trimeric SUN Proteins

Abstract: SUMMARY Linker of Nucleoskeleton and Cytoskeleton (LINC) complexes span the nuclear envelope and are composed of KASH and SUN proteins residing in the outer and inner nuclear membrane, respectively. LINC formation relies on direct binding of KASH and SUN in the perinuclear space. Thereby, molecular tethers are formed that can transmit forces for chromosome movements, nuclear migration and anchorage. We present crystal structures of the human SUN2-KASH1/2 complex, the core of the LINC complex. The SUN2 domain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
550
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(595 citation statements)
references
References 64 publications
22
550
2
Order By: Relevance
“…Our structural and biochemical studies strongly indicate that the SUN domain homotrimer is a primary KASH-binding unit, consistent with a recent independent report of the SUN-KASH complex structure [33]. However, it was recently found that both SUN proteins and KASH proteins can form high-order oligomers or clusters during specific cellular events [23,[34][35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our structural and biochemical studies strongly indicate that the SUN domain homotrimer is a primary KASH-binding unit, consistent with a recent independent report of the SUN-KASH complex structure [33]. However, it was recently found that both SUN proteins and KASH proteins can form high-order oligomers or clusters during specific cellular events [23,[34][35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 75%
“…A study by Sosa et al used sedimentation equilibrium analysis and suggested that the SUN complex was a homotrimer [33]. Nevertheless, large differences likely exist between the SUN-KASH microenvironment in cells and the solution conditions used for sedimentation equilibrium analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The flat cisternae of the ONM and INM are separated by the distance of the INS (about 50 nm), which is held constant by the LINC complex ( Fig. 1A) (Tzur et al 2006;Sosa et al 2012). The membrane bilayers of the INM and ONM cisternae are continuous with each other at nuclear pores (NPs), providing a conduit for membrane proteins to diffuse between the nuclear and cytoplasmic compartments ( Fig.…”
mentioning
confidence: 99%
“…Without binding the KASH domain, the KASHlid conformation is rather random. 40 The very C-terminal "PPPX" motif is positioned in a KASH pocket formed by S641, Y703, Y707, H628 and the cation-loop (Q593-C601), which explains why these four amino acids are critical for SUN-KASH interactions. 40 …”
mentioning
confidence: 99%
“…39,40 In this complex, three KASH domains are anchored in one cloverleaf-like trimer of SUN domains. The SUN domain protomer has several functional domains: an α-helical stalk, a compact β-sandwich core, a cation-loop, and a protruding anti-parallel β-sheet named the KASH-lid ( fig.…”
mentioning
confidence: 99%